Kedudukan Hak Atas Tanah yang Dimiliki Peserta Plasma yang Mengundurkan Diri (Studi Pada Pt. Anugerah Langkat Makmur) - Fahrizzal Nasty (Jurnal Perspektif Hukum, 2021)
In General, the most common partnership pattern in Indonesia in plasma nucleus such as PIR Pattern, KKPA Pattern, and PRP Pattern. PT. AnugerahLangkatMakmur (PT. ALAM) operates in oil palm plantations and factories; it has some KUDs (Village Unit Cooperatives) in Langkat Regency and Mandailing Natal Regency. The problem arises when some of their members withdraw and sell their srocks so that there is no certainty about their rights on the plantations which legal standing is the HGU (leasehold) that has not yet regulated or covered by laws and PP (Government Regulation); therefore, it is necessary to have legal breakthrough to settle the problems of cooperative pattern in the plasma plantations at PT. ALAM. Partnership Pattern is a must and the legal consequence of the position of land rights owned by plasma plantation whose members withdraw from the plasma membership (A Case Study at PT. ALAM). The partnership contract is a written form as specified in the Decree of The Minister of Agriculture No. 98/Permentan/OT.140/9/2013 on the Guidelines for Plantation Business License in Article 29, paragraph 2. In principle, the relationship between nucleus and plasma is specified in the Plasma Nucleus contract which explains specially the right and obligation and is made before a Notary. According to Law No. 39/2014, plasma is required to implement plantation business partnership and to facilitate smallholding plantations (in the term of 3 years since the HGU is in effect, it has to be implemented by the plantation company). The legal grounds which stipulates that HGU can be bequeathed is specified implicitly in Article 28, paragraph 2 of UUPA (The Land Act) which states that HGU can be transferred to other party. “Explicitly, the inheritance of HGU is specified in Article 16, paragraph 2, point e PP No. 40/1996 which indicates HGU occurs by inheritance. The land rights of the plasma members who have withdrawn will be transferred to KUD.